Effect of pH in Coagulation Bath on Polysulfone-based Membrane Formation and Its Performance Characteristics - Dwi Jayanti, Denik; Asnawati, Asnawati; Indarti, Dwi; S. Purwo Handoko, Donatus; Piluharto, Bambang (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2022)
One of the factors that determine the formation of the membrane is the solution in the coagulation bath (non-solvent). In this study, the effect of pH treatment on the coagulation bath solution on membrane formation and its effect on membrane performance will be studied. The pH of the coagulation bath used was pH 1, 6.8 and 12. As the results, physically the three pH treatments produced the same white (opaque) membrane. Through morphological analysis, it appears that the three pH treatments produced an asymmetric membrane consisting of a top layer and a sublayer. The surface of the membrane with pH 1 treatment showed a denser surface than the pH 6.8 and pH 12 treatments. The results of the membrane performance characterization showed that the membrane permeability coefficient of the membrane with pH treatment was in the following order pH 1 < pH 12 < pH 6.8. While the value of the rejection coefficient showed that the membrane treated at pH 1 did not detect rejection because there was no permeate coming out, while at the treatment at pH 6.8 and 12, the rejection coefficient values were 74% and 76%, respectively.